Clinical reasoning and clinical use of basic body awareness therapy in physiotherapy – a qualitative study?. (2nd January 2020) - Gard, Gunvor; Nyboe, Lene; Gyllensten, Amanda Lundvik
Abstract: Background: Clinical reasoning is the ability to integrate and apply different types of knowledge, weigh evidence critically and reflect upon the process to arrive at a diagnosis. Body awareness is an approach directed toward an awareness of how the body is used in terms of body function, behaviour, and interaction with self and others. Methods: In the present study, 36 physiotherapists (PTs) from 13 countries working with body awareness methods, mainly Basic Body Awareness Therapy (BBAT) in mental health were interviewed in six focus groups. Content analysis was used to analyse how the informants' reasoned around the concept of body awareness therapy, and how they use it in their clinical work with patients. Result: Body awareness was conceived as being in contact with sensations and emotions, to be able to control symptoms, such as pain, to find a balance and to develop one's identity by relating to oneself and others. BBAT was used as a whole body treatment, to promote balance and stability, to teach about body, movements, and coping strategies, to interact in a therapeutic approach and to be integrated with other methods and professionals. Conclusion: The present results can be used to improve the PTs clinical reasoning.